INOVASI BISNIS “ROMLAH SNACK" OLEH PEKERJA MIGRAN INDONESIA DI TAIWAN BERBASIS DESIGN THINKING DAN BUSINESS MODEL CANVAS PADA MASA COVID-19 - Hulam Mahmud; Beni Dwi Komara (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2022)
Many businessman fail when creating a business, it is due to a discrepancy between the business created and the problem of customer needs. For this reason, a product innovation is needed using business methods. Understand the process of designing Romlah Snack business innovations by PMI Taiwan participants using the Design Thinking and Business Model Canvas methods during the Covid-19 pandemic. The research used a descriptive qualitative method, and a PAR (Participatory Action Research) approach which was carried out to PMI Taiwan participants in an Online Entrepreneurial Workshop held by Muhammadiyah Gresik University with CLC-BJI Taiwan. The result of this study is, the beginning of the innovation of the Typical Indonesian snack business using the Design Thinking method. After conducting customer research, the most dominant customer problem emerged, namely indonesian snacks that were ordered online expired and destroyed. After searching and designing ideas through crazy 8 ideas and solution sketches, the Romlah Snack Online Store was found as the solution. Based on the results of Usability Testing indicates "Easy" and "Like"; Heuruistic Testing result score of 85.4%; and the results of the Impact Testing index of 100%, it is certain that the Romlah Snack online store answers consumer needs. Then a prototype is made to be tested to the customer. The making of the Business Model invites several stakeholders such as snack producers, etc. and then testing is carried out. And of the 5 assumptions, as many as 3 assumptions are valid and 2 are invalid.